Demonstration of a non-Tac peptide that binds interleukin 2: a potential participant in a multichain interleukin 2 receptor complex. - Tsudo, M (1986)
The interleukin 2 (IL-2) receptor system plays a key role in the T-cell immune response. Although IL-2 binding was reported to be restricted to the Tac peptide, we have identified an IL-2 binding peptide that does not react with anti-human IL-2 receptor monoclonal antibodies, including anti-Tac on MLA 144, a gibbon ape T-cell line. The MLA 144 cell line expressed 6800 IL-2 binding sites per cell with a low (Kd = 14 nM) affinity for human recombinant IL-2. Using cross-linking methodology, we demonstrated that the IL-2 binding peptide on MLA 144 is larger (Mr 75,000) than the Tac peptide, which has a Mr of 55,000. An IL-2 binding peptide of similar size (Mr 75,000) was also identified in addition to the Tac peptide (Mr 54,000-57,000) on Hut 102, a human T-cell lymphotrophic virus I-induced T-cell leukemia line, and phytohemagglutinin-activated normal human and gibbon ape lymphoblasts. Anti-Tac antibody did not block the binding of 125I-labeled IL-2 to MLA 144 cells. However, this antibody abolished the binding of 125I-labeled IL-2 not only to the Tac peptide on Hut 102 cells and normal lymphoblasts but also to the Mr 75,000 IL-2 binding peptide, suggesting that this latter peptide is associated with the Tac peptide to form the high-affinity IL-2 receptor complex.